Factors related to HIV infection among unmarried youth in rural areas of Southwest China. Issue 8 (3rd August 2018) - Zhang, Suhua; Jike, Chunnong; Yang, Shujuan; Liao, Qiang; Yu, Gang; Wang, Ke; Wang, Ju; Xiao, Lin; Wang, Qixing; Gong, Yuhan; Zhang, Jianxin; Bian, Shichao; et al.
ABSTRACT: We evaluated HIV prevalence among unmarried youth in rural areas of Liangshan Prefecture in southwest China over the period of 2011–2015, and the interactions between behaviors associated with HIV risk. We used HIV sentinel surveillance (HSS) data for our analysis. We used questionnaires to investigate information among unmarried youth aged 15 to 25 years and performed HIV testing. Multivariate logistic regression and path analysis were applied to explore associations between behavioral factors related with HIV infection. A total of 9536 unmarried youth were enrolled in this study, of whom 2.75% (262/9536) tested positive for HIV infection. Multivariate logistic regression showed that male gender, Yi ethnicity, illiteracy, out-migrating for work, needle sharing, and engaging in high-risk sexual behaviors were risk factors. Path analysis revealed that needle sharing had the greatest effect on HIV infection (0.267), followed by drug use (0.171), out-migrating for work (0.079), and high-risk sexual behavior (0.064). The epidemic of HIV infection among unmarried youth in rural areas of Liangshan Prefecture is severe, and prevention efforts should focus on high-risk groups such as youth who are male, Yi, illiterate, and out-migrating for work, and those who engage in high-risk sexual behaviors and needle sharing.